2021
DOI: 10.1097/md.0000000000027316
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of tibial plateau fractures involving the posterolateral column using the extended anterolateral approach

Abstract: To summarize the surgical technique and clinical effects of the extended anterolateral approach for the treatment of Schatzker type II and Schatzker type V/VI involving the posterolateral column tibial plateau. From January 2015 through December 2018, 28 patients with tibial plateau fractures involving the posterolateral column were included in the study. Among them, 16 patients were Schatzker type II treated using an extended anterolateral approach with lateral tibial locking compression plate fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…Our outcome of radiological assessment are comparable to other studies using IEF or internal implants (5,6). Mao et al reported there is no difference in the radiological score when assessment was done at 3 months and 12 months (13).…”
Section: Discussionsupporting
confidence: 88%
“…Our outcome of radiological assessment are comparable to other studies using IEF or internal implants (5,6). Mao et al reported there is no difference in the radiological score when assessment was done at 3 months and 12 months (13).…”
Section: Discussionsupporting
confidence: 88%
“…The included studies were conducted in the United States (2 studies, n = 44) 16,17 , China (17 studies, n = 413) 2,6,18-32 , India (3 studies, n = 85) 33-35 , Taiwan (5 studies, n = 162) 7,8,36-38 , South Korea (1 study, n = 18) 39 , and Turkey (1 study, n = 25) 40 . Fourteen studies used the anterior approach (10 open surgery, 4 arthroscopic surgery) 6-8,16,19,23,24,26,30,31,35,38-40 , 9 studies used the posterior approach 18,27-29,32-34,36,39 , and 11 studies used the anterior combined posterior approach 2,17,19-22,24,25,35,37,39 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the ROBINS-1 assessment tool 41 , 5 studies 16,23,25,26,40 were with a moderate risk of bias, 11 studies 6,17,19,24,27,28,30,31,36,37,39 were rated with a serious risk of bias, and 13 studies 2,7,8,18,20-22,29,32-35,38 were rated with a critical risk of bias (Appendices 1 and 2; http://links.lww.com/JBJSREV/A970). Twelve studies did not report the underlying diseases of the patients, which raises some concerns about adjusting confounding factors 2,6-8,17-22,24,27-39 .…”
Section: Resultsmentioning
confidence: 99%
“…By Chen HW et al and Mao W et al, an extended anterolateral approach has been created, showcasing outstanding visualization potential. Through this approach, the plate can be placed in a more posterior position [ 22 , 23 ]. Additionally, Giordano et al [ 24 ] proposed the “hoop plate” technique, involving the insertion of a horizontally preformed 1/3 tubular steel plate from the outer to inner sides through the posterior lateral surgical approach (Lobenhoffer approach) of fibular head osteotomy, providing support and embracing effects for fractures resulting from posterior lateral cortical rupture, displacement, and comminuted articular surfaces.…”
Section: Discussionmentioning
confidence: 99%